Characterisation of specific responses to three models of viral antigens in immunocompetent older adults - Beatriz Rioseras; Eva Bueno-García; Alejandra García-Torre; Rocío López-Martínez; Marco Antonio Moro-García; Sara Alonso-Álvarez; Victoria Menéndez-García; Alba Lluna-González; Alejandra Sousa-Fernández; Marta Fernández-Gudin; Laura Campos-Riopedre; Corina Castro-del Cueto; et al. (Immunity & Ageing)
Abstract Background Memory responses to the antigens that an individual encounters throughout life may vary with the intensity and duration of antigen contacts or even with changes in immune status over time. This work aims to characterise specific responses to latent CMV, seasonal influenza and novel SARS-CoV-2 infections in immunocompetent individuals over 60 years of age. Specific cellular and humoral responses were identified by IFN-γ and granzyme B release by ELISpot and antibody level measurement. T lymphocyte subpopulation phenotypes were characterised by flow cytometry. Results Cellular and humoral responses to these viruses were detected in almost all patients. Influenza and SARS-CoV-2 cellular responses were positively correlated. There was no significant correlation between CMV and influenza or SARS-CoV-2 responses although both were consistently lower in CMV-seropositive patients. CMV responses were negatively correlated with the levels of the least differentiated subsets of T lymphocytes, and positively correlated with the most differentiated ones, contrary to what happened with the influenza responses. Nevertheless, SARS-CoV-2 cellular responses were negatively correlated with the most differentiated CD8+ T lymphocytes, while humoral responses were negatively correlated with the least differentiated T lymphocytes. Responses to the three viruses were correlated with a Th1/Th2/Th17 balance in favour of Th1. Conclusions The results indicate that memory responses differ depending on the durability of the antigen stimulus. Cellular responses to novel pathogens resemble those generated by seasonal but not CMV infection. Subpopulation distribution and the level of specific T lymphocytes against previous pathogens could be used as immunocompetent status biomarkers in older adults reflecting their ability to generate memory responses to new pathogens.